Knowledge networks, which roles for regions and for different communication modes? - Marina Van Geenhuizen; Holmer Doornbos (European Regional Science Association (ERSA), 2004)
Knowledge Networks, which Roles for Regions and for Different Communication Modes? Marina van Geenhuizen and Holmer Doornbos This paper presents first results of a study on how knowledge networks of companies are structured and how these are used. It questions the idea that knowledge networks are increasingly regional with a large importance of face-to-face contacts within the region. To this purpose the paper aims to identify the spatial pattern of knowledge contacts (from regional to international) and the use of particular modes of communication, like electronic ones and face-to face-contact, the latter within the region but also somewhere else in the world using air transport. First, theories on the behavior of companies in knowledge networks and theories on the use of communication modes are discussed. This is followed by an empirical analysis based on a selected sample of companies in two regions of the Netherlands: Southeast Brabant and the northern part of the Randstad. The empirical study makes use of rough set data analysis to identify differences between companies in the geographical spread of knowledge contacts and in the communication modes in using these contacts. Key words: Regions, Knowledge networks, Communication modes, Knolwedge contacts, Substitution, the Netherlands
Keywords: 330; Regions; Knowledge networks; Communication modes; Knolwedge contacts; Substitution; the Netherlands